EMOTIONS IN BUSINESS ORGANIZATIONS: AN EMPIRICAL STUDY ON RELATION BETWEEN EMOTIONS - Ercil, Yavuz; Varoglu, Demet (PEOPLE: International Journal of Social Sciences, 2017)
This paper aims to clarify the effects of emotions on organizational life based on the complex adaptive systems (CAS) approach and proposes a new frame for defining and examining emotions in organizations. In this frame, following the CAS approach, emotional interaction between drivers and attractors within organizations is shown. The proposed framework was tested by conducting a survey on a cross-sectional sample of 325 national and international, public and private sector employees. Free or passive word association was requested from the participants of the survey. The research study was designed and conducted in three stages. At the first stage, the emotional terms that are mostly used in business organizations were sought out.At the second stage, emotional associations were asked to participants. At the third stage, affects of these emotions were examined in terms of the CAS rules.The results indicate that emotions such as anger, fear, and sadness act as source emotions to other (result) emotions. Although there were no significant differences among people from different cultures in terms of how emotional concepts were defined, emotions changed with organizational characteristics.